Psychological factors influencing the feeling of loneliness in female students with hearing impairments - Baranauskienė, Ingrida; Kovalenko, Alla; Leonova, Inna (Special Education, 2020)
The article presents the study results on the factors influencing the emergence of the feeling of loneliness in female students with hearing impairments. The results obtained indicate the presence of the feeling of loneliness in students with hearing impairments, especially, this feeling emerges most often in the family sphere. The feeling of loneliness is associated not only with interpersonal relationships, but also with personal traits, attitudes, needs. The sources of irritability and emotional instability for female students with hearing impairments are: insufficient satisfaction of their need for social and cultural communication, existing gender conflicts between partners, which are caused by social stereotypes and gender inequality. The main reasons for the feeling of loneliness in female students with hearing impairments are fears: of loneliness, dependence, rejection by others, both in interpersonal and social relations, as well as social anxiety. The feeling of loneliness emerges under the influence of the following factors: fear of communication, interpersonal relationships, personal characteristics, as well as dissatisfaction with one’s own life quality. Female students with hearing impairments require special attention from university staff to integrate them into the educational environment, establish contacts with peers and family members.